Promoter methylation of the SALL2 tumor suppressor gene in ovarian cancers. Issue 3 (12th December 2012) - Sung, Chang K.; Li, Dawei; Andrews, Erik; Drapkin, Ronny; Benjamin, Thomas
Abstract : The SALL2 gene product and transcription factor p150 were first identified in a search for tumor suppressors targeted for inactivation by the oncogenic mouse polyoma virus. SALL2 has also been identified as a cellular quiescence factor, essential for cells to enter and remain in a state of growth arrest under conditions of serum deprivation. p150 is a transcriptional activator of p21Cip1/Waf1 and BAX, sharing important growth arrest and proapoptotic properties with p53. It also acts as a repressor of c‐myc. Restoration of SALL2 expression in cells derived from a human ovarian carcinoma (OVCA) suppresses growth of the cells in immunodeficient mice. Here we examine the pattern of p150 expression in the normal human ovary, in OVCA‐derived cell lines and in primary ovarian carcinomas. Immunohistochemical staining showed that p150 is highly expressed in surface epithelial cells of the normal human ovary. Expression is exclusively from the P2 promoter governing the E1A splice variant of p150. The P2 promoter is CpG‐rich and susceptible to methylation silencing. p150 expression was restored in OVCA cell lines following growth in the presence of 5‐azacytidine. In a survey of 210 cases of OVCA, roughly 90% across major and minor histological types failed to show expression of the protein. Immunological and biochemical approaches were used to show hypermethylation of the SALL2 P2 promoter in OVCA‐derived cell lines and in a majority of primary tumors. These results bring together molecular biological and clinical evidence in support of a role of SALL2 as a suppressor of ovarian cancers. Highlights: ► p150, product of the SALL2 gene, is a target of the polyoma virus large T antigen. ► p150 is a putative tumor suppressor with p53‐like functions. ► p150 is highly expressed in surface epithelial cells of the normal human ovary. ► p150 is absent or greatly diminished in a majority of human ovarian cancers. ► Loss of p150 expression is due to methylation of the SALL2 P2 promoter.